Sistema de monitoramento da frequência cardíaca via lógica fuzzy em bicicleta ergométrica com microgeração de energia - Müller, Lilian Vaselquiu (2019)
This research presents the development of a Fuzzy logic-based recommendation system that supervises the user's heart rate to indicates the adequate rotation according to the measured heart rate and load. Simultaneously with the recommendation system,a micro-generation renewable energy system was made through physical exertion on a stationary bicycle. It was coupled to an ergometric bicycle, which was installed in the laboratory of electrical machines of the DAELT (Department of Electrotechnology) of the Federal Technological University of Paraná -UTFPR Curitiba, an alternator AC to on the inertia flywheel, thus generating electric energy according to the effort applied to the pedal. In order to ensure that the cyclist manages sustainable electric energy, for a certain period and with safety to his health. For the construction of the heart rate monitoring system, ARDUINO® was used as an electronic prototyping platform that uses an AT Mega 2560 microcontroller. The board of this platform is called Arduino Mega 2560. The device created, hardware and software, are presented in detail and the results of the tests performed with 3 users (practitioners between 23 and 40 years) showed the adequate rotation for each one and that the heart rates of these three practitioners remained between minimum , optimal and maximum, thus ensuring the physical integrity of these users in sustainable power generation. The values achieved in the tests by the practitioners were compared to simulated values in the MATLAB® software.